THE PRELIMINARY STUDY ON THE APPLICATION OF JOINT TENANCY IN MALAYSIA - Nur Akmal Adnan; Azhani Arshad; Rahmawati Mohd Yusoff; Akmal Hidayah Halim; Syuhaeda Aeni Mat Ali (Journal of Islamic, Social, Economics and Development, 2022)
Under common law, the concept of joint tenancy means that if any joint tenant dies, the left portion of the deceased will obligatorily be conceded to the surviving joint tenant and will not form part of the deceased's estate. A joint tenancy contract is acknowledged by the National Land Code (Penang and Malacca Titles) Act 1963, but the National Land Code 1965 only recognises common tenancy. Consequently, the ownership will be shared not only during the lifetime of the joint tenant but extended even after death and will be considered part of the deceased joint tenant's estate. This caused hardship to the surviving joint owner, especially when the joint owners had jointly acquired and developed property. Hence, it is a timely action to explore the concept of joint tenancy under the common law and examine its validity under the law of succession in Malaysia. This research is based on qualitative research and analysis of the primary and secondary materials through the governing statutes, reported cases, and data obtained from the respective administrative bodies. For the comparative analysis, the research also explores the law and practice of joint tenancy in Singapore and Australia for the dual legal and Torrens systems, respectively. It is predicted that the joint tenancy application would give the proprietor more options in planning his property's management and rightly give the surviving joint tenant the full enjoyment of the property.